Handbook of pharmaceutical excipients - Sheskey, Paul J.; Cook, Walter G.; Cable, Colin G. (London ; Washington DC : Pharmaceutical Press ; American Pharmacists Association, 2017)
The Handbook of Pharmaceutical Excipients is internationally recognised as the authoritative source of information on pharmaceutical excipients giving a comprehensive guide to uses, properties and safety.
New Formulation Considerations and Related Information chapters on: - Functional Categories of Pharmaceutical Excipients - Pharmaceutical Excipients in Pediatric Formulations - The Selection of Excipients for Oral Solid Dosage Forms - Reactive Components in Pharmaceutical Excipients Over 400 Monographs benefiting from a standardized, easy-to-use template including: - pharmacopoeial information from the UK, Europe, Japan and the United States where relevant - non-proprietary names and synonyms - chemical name and structure, CAS Registry number, empirical formula, molecular weight - functional category, applications and incompatibilities - material description and typical excipient properties - safety, stability, storage and handling information - method of drug manufacture - related substances - primary references - editorial comments - author details and revision date 6 Appendices: - Suppliers directory - List of Monographs by Functional Category - List of Related Substances - List of Excipients by `E' number - List of Excipients by `EINECS' number - List of Excipients by `CAS' number
Previous edition: 2012.
Includes bibliographical references and index.
PHR
Trim Education
Keywords: Excipients -- Handbooks, manuals, etc; Technology, Pharmaceutical -- Handbooks; Excipients -- Handbooks; Pharmacy